2008
DOI: 10.1093/rheumatology/kem307
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound of skin involvement in systemic sclerosis reflects oedema, extension and severity in early disease

Abstract: In SSc patients with short disease duration, high-frequency ultrasound can identify the oedematous phase that may precede palpable skin involvement and may thus be useful to identify patients with diffuse skin involvement very early in the disease process. Ultrasound measurements also reflect the severity of the overall skin involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 14 publications
11
120
2
1
Order By: Relevance
“…The authors concluded that HFUS may allow for the identification of patients with diffuse skin involvement very early in the disease process, and in assessing the severity of the skin disease. 51 Ultrasound has also been used to interpret treatment outcome in inflammatory dermatoses. In skin disorders such as morphea and sclerosis, response to treatment is commonly assessed using a scoring system based on palpation.…”
Section: Inflammatory Diseases/infectious Diseases/ Benign Neoplasmsmentioning
confidence: 99%
“…The authors concluded that HFUS may allow for the identification of patients with diffuse skin involvement very early in the disease process, and in assessing the severity of the skin disease. 51 Ultrasound has also been used to interpret treatment outcome in inflammatory dermatoses. In skin disorders such as morphea and sclerosis, response to treatment is commonly assessed using a scoring system based on palpation.…”
Section: Inflammatory Diseases/infectious Diseases/ Benign Neoplasmsmentioning
confidence: 99%
“…Also problematic is the need for investigator training, varying degrees of examiner's experience, and uncertainty about the sensitivity of the scores over time [13][14][15][16][17]. Several objective methods for assessment of scleroderma have been proposed, including ultrasound, X-ray, MRI, indentation, and durometry [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The cutaneous involvement varies from limited to diffuse skin fibrosis 1 . High-frequency and high-resolution ultrasound probes offer the opportunity to evaluate not only skin thickness but also its echogenicity 2 . The mechanical properties of tissue depend on the constituent macromolecules, such as fat and collagen, and on the structural organization.…”
mentioning
confidence: 99%